2012
DOI: 10.7882/az.2012.009
|View full text |Cite
|
Sign up to set email alerts
|

The dietary preferences of koalas,Phascolarctos cinereus, in southwest Queensland

Abstract: The koala population in southwest Queensland is a large low-density population of important conservation value which is vulnerable to habitat loss, drought and climate change. The nutrient quality of Eucalyptus food trees favoured by koalas is an important factor influencing the survival of the koala on a low-nutrient-and-high-toxin diet. This study investigated the relationship between the diet of koalas, and food tree characteristics. Vegetation surveys, cuticle analysis and leaf chemical analysis were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…We calculated the proportion of primary and secondary habitat in each landscape, as previous research has found that the amount of high-quality habitat is important for koalas in Queensland and New South Wales Smith et al, 2013a). Primary habitat was dominated by E. camaldulensis, which forms the majority of the koala's diet and tree use in this region (Seabrook et al, 2011;Wu et al, 2012). Secondary habitat was dominated by E. coolabah, E. populnea, E. ochrophloia and E. thozetiana.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…We calculated the proportion of primary and secondary habitat in each landscape, as previous research has found that the amount of high-quality habitat is important for koalas in Queensland and New South Wales Smith et al, 2013a). Primary habitat was dominated by E. camaldulensis, which forms the majority of the koala's diet and tree use in this region (Seabrook et al, 2011;Wu et al, 2012). Secondary habitat was dominated by E. coolabah, E. populnea, E. ochrophloia and E. thozetiana.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Previous studies have found that the water content of eucalypt leaves across Queensland ranged between 39-65% wet weight (Munks et al 1996, Ellis et al 2002, Clifton 2010, Wu et al 2012.…”
Section: Foliar Chemistry Of Eucalyptusmentioning
confidence: 98%
“…Water availability to trees varies both spatially and temporally which influences leaf chemistry in different ways. In semi-arid areas of Queensland, Eucalyptus trees occurring along creek-lines, where more folivores also occur, had higher leaf moisture than in trees growing far from creek-lines (Munks et al 1996, Wu et al 2012). In addition, presence of surface water was positively associated with leaf moisture (Wu et al 2012) and surface water can make up to 50% of the water source to trees when it is available in long-term .…”
Section: Environmental Variation and Genus Eucalyptus Foliar Chemistrymentioning
confidence: 99%
See 2 more Smart Citations